2018
DOI: 10.23937/2469-5769/1510031
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia Caused by Klebsiella Pneumoniae in Preterm Newborn Infants

Abstract: Background: The basis for the study is the high morbidity and mortality in premature infants with ventilator-associated pneumonia (VAP). There is a high incidence of complications (sepsis, bronchopulmonary dysplasia). Methods: A detailed analysis of the clinical course of VAP caused by Klebsiella pneumoniae in 14 premature infants was conducted. The sensitivity of Klebsiella pneumoniae strains to 18 antibiotics was studied by the method of standard discs. Results: Severe pneumonia had 10 infants, moderate stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…(39) The study of Ghotaslou et al reported that risk factors for bacteremia were catheterization, hyperalimentation, and mechanical ventilation a predominance were seen in male neonates, low birth weight (35) . In over all clinical features Respiratory distress was reported in 69.5%.of the pateints it was 40% in Ghotaslou etal study and also seen in other studies , (21,23 ,24,25,31,38,43) 61.5% need Mechanical ventilation as many other study 26,43,44 Hyper bilirubenemia in 53.8% in malaki study it was 86% 14.3% in Ghotaslou etal study (27,35) . Necrotizing enterocolities was 30.8% in our study.…”
Section: Discussionmentioning
confidence: 51%
“…(39) The study of Ghotaslou et al reported that risk factors for bacteremia were catheterization, hyperalimentation, and mechanical ventilation a predominance were seen in male neonates, low birth weight (35) . In over all clinical features Respiratory distress was reported in 69.5%.of the pateints it was 40% in Ghotaslou etal study and also seen in other studies , (21,23 ,24,25,31,38,43) 61.5% need Mechanical ventilation as many other study 26,43,44 Hyper bilirubenemia in 53.8% in malaki study it was 86% 14.3% in Ghotaslou etal study (27,35) . Necrotizing enterocolities was 30.8% in our study.…”
Section: Discussionmentioning
confidence: 51%